2022
DOI: 10.1007/s40145-021-0544-4
|View full text |Cite
|
Sign up to set email alerts
|

Remarkably enhanced piezo-photocatalytic performance in BaTiO3/CuO heterostructures for organic pollutant degradation

Abstract: Introducing polarization field of piezoelectric materials is an effective strategy to improve photocatalytic performance. In this study, a new type of BaTiO3/CuO heterostructure catalyst was designed and synthesized to achieve high piezo-photocatalytic activity through the synergy of heterojunction and piezoelectric effect. The BaTiO3/CuO heterostructure shows a significantly enhanced piezo-photocatalytic degradation efficiency of organic pollutants compared with the individual BaTiO3 nanowires (NWs) and CuO n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(24 citation statements)
references
References 43 publications
(35 reference statements)
0
24
0
Order By: Relevance
“…However, because interfacial strain requires different substrates with distinct lattice constants, comparison of such strain effect faces the severe challenge that interfacial strain may cause cobaltate stoichiometry offset, octahedral rotation, etc. [5][6][7][8] Thus an in situ strain change on the OER performance of the singlecrystal cobaltate is highly desired to maximally reduce the uncertainty from individual samples.…”
Section: Introductionmentioning
confidence: 99%
“…However, because interfacial strain requires different substrates with distinct lattice constants, comparison of such strain effect faces the severe challenge that interfacial strain may cause cobaltate stoichiometry offset, octahedral rotation, etc. [5][6][7][8] Thus an in situ strain change on the OER performance of the singlecrystal cobaltate is highly desired to maximally reduce the uncertainty from individual samples.…”
Section: Introductionmentioning
confidence: 99%
“…With the increase in population, the demand for drinking water has surged, but the sources of drinking water have decreased due to water pollution. 1–4 Sewage treatment and drinking water production have become the factors restricting economic development. Solar energy is considered a sustainable and pollution-free energy source.…”
Section: Introductionmentioning
confidence: 99%
“…The BT nanocubes/cuboids with selectively deposited Ag nanoparticles on the positively polar facets showed high-piezocatalytic activity in both dye and nondye pollutants degradation . It can be found that most of these studies about the improvement of piezocatalytic activity of BT-based materials have mainly focused on the morphology regulation, , noble metals’ deposition, , doping, , and construction of heterojunction. , In addition, the piezoelectric activities of materials also play a crucial role in the piezocatalytic process. However, there are few reports on enhancing the piezocatalytic performance in BT-based materials by promoting the piezoelectric activity of the piezocatalysts .…”
Section: Introductionmentioning
confidence: 99%